PELATIHAN PEMANFAATAN ARTIFICIAL INTELLIGENCE UNTUK MEMBUAT FOTO PROMOSI BAGI UMKM LEK YATI DI KOTA SALATIGA - Hendrawan, Angga (Jurnal Pengabdian Bukit Pengharapan, 2025)
The need for product photography is inseparable from promotional activities aimed at attracting potential customers. Generally, creating high-quality product photos requires specialized equipment, technical skills, or the services of a professional photographer—all of which entail significant costs and are often inaccessible to micro, small, and medium enterprises (MSMEs) with limited financial resources. This community service activity aims to train the owner of the MSME “Lek Yati” to create product photos using simple tools and low-cost methods through ChatGPT, an artificial intelligence (AI) platform based on text-to-image generation. The results of the activity show that participants were able to operate AI tools to produce more appealing product images for promotional purposes. This training provides the partner with the opportunity to independently produce promotional materials without being burdened by costs.